A comparative experimental study of the hygroscopic and mechanical behaviors of electrospun nanofiber membranes and solution‐cast films of polybenzimidazole. Issue 39 (15th July 2020) - Zholobko, Oksana; Wu, Xiang‐Fa; Zhou, Zhengping; Aulich, Ted; Thakare, Jivan; Hurley, John
Abstract: This article reports a comparative experimental study of the hygroscopic and mechanical behaviors of electrospun polybenzimidazole (PBI) nanofiber membranes and solution‐cast PBI films. As‐electrospun nonwoven PBI nanofiber mats (with the nanofiber diameter of 250 nm) were heat‐pressed under controlled temperature, pressure and duration for the study; lab‐made solution‐cast PBI films and commercially available PBI films (the PBI Performance Product Inc., Charlotte, NC) were used as the control samples. Thermogravimetric and microtensile tests were utilized to characterize the hygroscopic (moisture absorption) and mechanical properties of the PBI nanofiber membranes at varying heat‐pressing conditions, which were further compared to those of solution‐cast PBI films. Experimental results indicated that the PBI nanofiber membranes carried slightly higher thermal stability and less hygroscopic properties than those of solution‐cast PBI films. In addition, heat‐pressing conditions significantly influenced the mechanical properties of the resulting PBI nanofiber membranes. The stiffness and tensile strength increase with increasing either the heat‐pressing pressure or duration, and relevant mechanisms were explored. The present study provides a rational understanding of the hygroscopic and mechanical behaviors of electrospun PBI nanofiber membranes and solution‐cast PBI films that are beneficial to their reliable cutting‐edge applications in high‐temperature filtration, polymer electrolyte membranes (PEMs), etc. Abstract :